Digitalization Through Creative Writing on social media - Eddy Soeryanto Soegoto; M Mulyanto; Sri Yuliawati; Adhea Vinora Putri (International Journal of Research and Applied Technology (INJURATECH), 2022)
The purpose of this study is to determine the extent of the role of social media on consumer interest in using the services of a copywriter. Because social media can be used as a promotional medium by using captions and also good visuals, which can be written according to the wishes of the businessman in attracting the attention of consumers. Consumers also don't need to come directly to the place or office of the copywriter, they just need to use Instagram social media for sources of information related to working days and hours, arrange meeting schedules, and so on. This study uses a qualitative descriptive research method by conducting a literature study on various studies. The results of this study are expected to build brand awareness so that it can increase interest in services sold with digital marketing techniques carried out by service owners. In addition, using Instagram social media can also make it easier for business owners and consumers. This of course can increase sales revenue.